Pengaruh Larutan Daun Ketapang (Terminalia catappa) Terhadap Daya Tetas Telur dan Kelangsungan Hidup Larva Ikan Lele Sangkuriang (Clarias gariepinus) - Maria Desi Deria Banase; Ni Putu Dian Kusuma; Pieter Amalo (Samakia : Jurnal Ilmu Perikanan, 2024)
Production increase in the field of freshwater fisheries what needs to be considered is the quality of eggs and seeds as well as the parent, cultivation activities often found problems with eggs caused by lack of oxygen to inhibit embryonic development. In addition, eggs are often attacked by fungi, resulting in rotting eggs. Ketapang leaf extract can prevent and treat fish diseases caused by bacteria. Ketapang leaves contain tannin and flavonoid compounds that function as anti-bacterial. This study aims to determine the effect of egg soaking in Ketapang leaf solution on the degree of hatching of Sangkuriang catfish eggs. The research was carried out in March 2023 at the freshwater fish farming hatchery, Ngrajek Village, Magelang Regency, East Java. The study used a complete randomized design with three treatments and three repetitions, namely treatment A as much as 5 ml of Ketapang leaf solution, B as much as 7 ml of Ketapang leaf solution, and C (control) without giving Ketapang leaf solution.